Durable Metastatic Melanoma Remission Following Pembrolizumab and Radiotherapy: A Case Report of Prophylactic Immunosuppression in a Patient with Myasthenia Gravis and Immune-Mediated Colitis - Moradi, Luke A.; Clark, Curtis A.; Schneider, Craig S.; Deshane, Alok S.; Dobelbower, Michael C. (Frontiers in Immunology, 2021)
Immune checkpoint inhibitor (ICIs) and radiotherapy combinations for various metastatic cancers are increasingly utilized, yet the augmentation of anti-cancer immunity including distant tumor responses by radiotherapy (RT) remains ill-characterized. Immunosuppressive tumor microenvironments and defective anti-tumor immune activation including immune-related adverse events (irAEs) likely limit dramatic immuno-radiotherapy combinations, though it remains unclear which immune characteristics mediate dramatic systemic tumor regression in only a small subset of patients. Moreover, the efficacy of ICI treatment in patients receiving immunosuppressive therapies for autoimmune conditions or irAEs is convoluted, yet clinically valuable. Here, we report a case of a 75-year-old man with myasthenia gravis and metastatic melanoma who experienced complete and durable systemic regression after receiving pembrolizumab and single-lesion RT while on prednisone for myasthenia gravis prophylaxis and vedolizumab for immune-mediated colitis after previously experiencing mixed response on pembrolizumab monotherapy. We discuss the potential paradoxical effects and clinical considerations of immunosuppressive regiments in patients with underlying autoimmune disease or adverse immune reactions while receiving immuno-radiotherapy combinations.